SAT0005 Human C-Type Lectin Domain Family 4, Member C Gene Expression Level Helps Predict Future Clinical Response to Tabalumab Blockade of Baff in Rheumatoid Arthritis. (23rd January 2014) - Dow, E. R.; Banerjee, P.; Penny, M. A.; Nantz, E.; Stepaniants, S.; Ho, A.; Komocsar, W. J.; Berclaz, P.-Y.; Hoffman, R. W.
Abstract : Background: Patients with rheumatoid arthritis (RA) exhibit substantial variability in both the magnitude and duration of their clinical response to treatment. Despite considerable research, no biomarker has reproducibly been shown to predict likelihood of clinical response to biologic therapy. There remains significant unmet medical need to identify patients who will have a meaningful clinical response to treatment prior to drug exposure. We have recently demonstrated efficacy of BAFF blockade in RA using tabalumab (previously known as LY2127399) 1 . We have now used gene expression profiling of whole blood mRNA, obtained prior to drug exposure, to identify a predictive gene expression pattern that helps identify patients that are highly likely to respond to treatment with tabalumab. Methods: Whole blood mRNA was obtained at baseline from 158 RA subjects with an inadequate response to methotrexate enrolled in a phase 2 randomized trial in which patientsreceived placebo, 1, 3, 10, 30, 60 or 120 mg of tabalumab every 4 weeks over 24 weeks. Clinical results of BAFF blockade in RA of this study have recently been reported 1 . In addition to the RA subjects (152 samples passed quality control), samples from 30 healthy blood donor controls were analyzed using Affymetrix U133 Plus 2.0 expression arrays to determine gene expression, and data were compared after normalization using Robust Multichip Average (RMA) algorithm 3 . Human C-type Lectin Domain Family 4, Member C (CLEC4C) qPCR was performed in validated assays at Covance Genomics Seattle using primers and probes obtained from ABI. Statistical analyses were performed using Messina 2, two sample t-test or regression modeling. Results: There was a bimodal distribution of CLEC4C mRNA in whole blood from RA patients and controls at baseline. The mean level of CLEC4C gene expression measured by Affymetrix was lower in patients than in controls. Mean expression after normalization for patients (n=152) is 5.79 with a range of 3.18 to 9.69. Mean expression for control healthy blood donors (n=30) is 6.88, range is 4.36 to 9.02. Among patients, those with higher levels of CLEC4C gene expression were more likely to respond to tabalumab (as measured by ACR-N). Messina analysis 2 at baseline identified both CLEC4C probe sets as having the largest margin when comparing responder and non-responder group outcome at week 16 using ACR-N/DAS28. A two sample t-test on the same data was significant (p<0.0007). These expression findings from selected Affymetrix probe sets were validated using qPCR; for CLEC4C the change in threshold cycle versus ACR-N was statically significant after correction for multiple comparisons using False Discovery Rate (FDR) and Bonferroni techniques (FDR p=0.013, Bonferroni p=0.013). Conclusions: The subgroup of RA patients with higher levels of CLEC4C mRNA expression at baseline was significantly more likely to respond to treatment with tabalumab. Independent replication of these hypothesis generating findings is now in progress in a large phase 3 clinical trial of tabalumab. References: Genovese et al. Ann Rheum Dis 2011;70(Suppl3):71 Pinese et al PLoS ONE 4(4): e5337. Irizarry et al Nucleic Acids Research 2003 31(4):e15 Disclosure of Interest: E. Dow Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, P. Banerjee Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, M. Penny Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, E. Nantz Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. Stepaniants Employee of: Covance Genomics Seattle, A. Ho Employee of: Covance Genomics Seattle, W. Komocsar Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, P.-Y. Berclaz Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, R. Hoffman Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company